Cheyenne amber - Anderson, Catherine (Adeline Catherine) (New York : Signet, 2013)
After her infant son is kidnapped, Laura hires the rough- edged, dangerously handsome Deke to track down those responsible.
Keywords: Man-woman relationships -- Fiction; Abduction -- Fiction; Love stories